The pea TCP transcription factor PsBRC1 acts downstream of strigolactones to control shoot branching - Braun,N; de,Saint Germain A; Pillot,J-P; Boutet-Mercey,S; Dalmais,M; Antoniadi,I; Li,X; Maia-Grondard,A; Le,Signor C; Bouteiller,N; Luo,D; Bendahmane,A; et al. (Plant Physiology, 2011)
The function of PsBRC1, the pea (Pisum sativum) homolog of the maize (Zea mays) TEOSINTE BRANCHED1 and the Arabidopsis (Arabidopsis thaliana) BRANCHED1 (AtBRC1) genes, was investigated. The pea Psbrc1 mutant displays an increased shoot-branching phenotype, is able to synthesize strigolactone (SL), and does not respond to SL application. The level of pleiotropy of the SL-deficient ramosus1 (rms1) mutant is higher than in the Psbrc1 mutant, rms1 exhibiting a relatively dwarf phenotype and more extensive branching at upper nodes. The PsBRC1 gene is mostly expressed in the axillary bud and is transcriptionally up-regulated by direct application of the synthetic SL GR24 and down-regulated by the cytokinin (CK) 6-benzylaminopurine. The results suggest that PsBRC1 may have a role in integrating SL and CK signals and that SLs act directly within the bud to regulate its outgrowth. However, the Psbrc1 mutant responds to 6-benzylaminopurine application and decapitation by increasing axillary bud length, implicating a PsBRC1-independent component of the CK response in sustained bud growth. In contrast to other SL-related mutants, the Psbrc1 mutation does not cause a decrease in the CK zeatin riboside in the xylem sap or a strong increase in RMS1 transcript levels, suggesting that the RMS2-dependent feedback is not activated in this mutant. Surprisingly, the double rms1 Psbrc1 mutant displays a strong increase in numbers of branches at cotyledonary nodes, whereas branching at upper nodes is not significantly higher than the branching in rms1. This phenotype indicates a localized regulation of branching at these nodes specific to pea.